Analysis of the impact of adequacy on operational information technology processes to the requirements of the Sarbanes-Oxley act in a financial company - Arrivabene, Adriano (2021)
In the nineties, some US publicly traded companies defrauded their financial results, generating an image of unreal stability. This situation affected the degree of investor confidence, creating the Sarbanes-Oxley Act (SOX), which forced companies to adapt their processes, including those of Information Technology (IT) to the rules of that law. The objective of this work was to analyze the impact caused to the IT operational processes with their adaptation to the requirements of the SOX in a company in the financial sector. This objective was sought by analyzing the information obtained, comparing the situations of various IT operational processes in the Pre and Post SOX periods. Descriptive and exploratory research methodology was adopted. Along with the bibliographic survey, real data reported by professionals who participated in the activities covered in the work were collected through the application of unstructured interviews. The bibliographic survey showed that, although important, there are few works that present the impact and the adequacy of the SOX to their IT operational processes. Most of them are related to process management, which reveals the importance of this work. The results showed the need to implement SOX control processes, such as the creation of a control table to monitor the processing, also showed that there were increases in the processing times of the batch routines and processing of the online applications due to the increase in information generated and stored. It was concluded that there was an impact on the operational processes with their adaptation to the requirements of SOX.